Fire Alarm System Design Based on PLC Pi Pico at MCC XYZ Company - Gama Dhuhry Avreliyanda; Rini Puji Astutik (PROGRAM STUDI TEKNIK ELEKTRO, 2024)
As is known, the development of technology today is much faster than in previous eras. Especially in the field of industrial automation systems. With the rapid development of technology, one of its functions is to facilitate human work with the existence of an automatic control system. MCC or known as the motor control center is equipment in industrial applications that is used to control motors centrally on a panel. This article describes the design and prototype method for a fire alarm system based on the PLC pi pico at the MCC XYZ company. The work process in this system is to monitor fires in the MCC room of the XYZ company, this system is controlled using the PLC Rapsberry pi pico. While SCADA (Supervisory Control and Data Acquisition) is used as a monitoring system with the MQ 2 sensor, Flame detector sensor, pushbutton as a temperature sensor and can also be accessed via the melsec protocol. The output is in the form of an alarm and a pump. The results of this study show that the tool works well and is able to help minimize fires in the area.